A SOCIOCOGNITIVE-TRANSFORMATIVE APPROACH TO TEACHING WRITING - Barrot, Jessie (Universitas Pendidikan Indonesia, 2015)
Abstract. This article reports some of the compelling concerns in using various approaches to teaching writing. On this note, this paper provides an alternative teaching framework for the teaching of ESL writing to address these concerns. This sociocognitive-transformative framework incorporates the cognitive, social, cultural, and transformative components of learning. Specifically, the discussion covers three sections that shed light on the theoretical underpinning, the design, and procedure on how the proposed approach can be realized in ESL writing classrooms. It is also hoped that through this approach, the teaching and learning of writing would lead to producing 21st century learners capable of surviving this highly globalized and knowledge-based society.